THE EFFECT OF THE THREE-STEP INTERVIEW TECHNIQUE ON ELEVENTH-GRADE STUDENTS’ SPEAKING SKILLS - Aldi; Yuyun Hendrety; Rahma Dianti (Program Pendidikan Bahasa Inggris Universitas Tridinanti, 2025)
Enhancing students' speaking skills remains a major obstacle in English instruction, especially in secondary schools with vocational programs where effective communication is crucial. This study investigated whether eleventh-grade students at SMK PGRI 2 Palembang might improve their speaking proficiency by using the three-step interview technique. A quantitative method with a quasi-experimental design was employed, involving 42 students selected through purposive sampling, with 22 assigned to the experimental group and 20 to the control group. Data were collected through a speaking test. The obtained data were analyzed using the Wilcoxon signed-rank test and the Mann-Whitney U test, since the data were not normally distributed. The Wilcoxon Signed-Rank test revealed a significant improvement in speaking achievement within the experimental group (Asymp. Sig. = 0.000 < 0.05), indicating that the three-step interview technique effectively fostered students’ speaking achievement. However, the Mann-Whitney U test showed no significant difference between the experimental and control groups (Asymp. Sig. = 0.192 > 0.05), suggesting that the technique did not outperform traditional methods in this sample. These findings imply that while the three-step interview technique can be a useful classroom strategy to support speaking development, further research with larger samples and diverse contexts is recommended to evaluate its comparative effectiveness.